When we are kind = Nihá'ádaahwiinít'ı̨́́įgo - Gray Smith, Monique, 1968- (Orca Book Publishers, 2020)
"This dual-language beautiful picture book looks at how the simple act of being kind, to others and oneself, affects all aspects of a child's life. In English and Diné."--